2020
DOI: 10.1186/s13049-020-00725-w
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pre-hospital evaluations in ruling out invasive chest stab wounds

Abstract: Background Some guidelines advocate for managing patients with penetrating thoracic wounds in trauma centres with cardiothoracic surgery. This systematic approach is questionable. Only 15% of these patients require surgery. It is known that clinical examination fails to detect hemopneumothorax in penetrating trauma. However, no studies have evaluated the combined diagnostic performance of vital signs and the clinical evaluation of wounds. The clinical characteristics of wounds have not been investigated. We ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A certain degree of over-triage of patients initially presenting without significant hemodynamic- or ventilatory compromise by HEMS teams in this respect, is almost inevitable. Previous studies have demonstrated that the accuracy of clinical examination to establish the degree of bleeding and potential for internal damage after penetrating injury is poor [ 14 , 27 , 28 ]. Our clinical judgement in these patients is often obscured, as the scene of the incident is often not witnessed (making it hard to estimate the amount of blood loss), and the physiological response to blood loss in the patients may differ from non-penetrating injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A certain degree of over-triage of patients initially presenting without significant hemodynamic- or ventilatory compromise by HEMS teams in this respect, is almost inevitable. Previous studies have demonstrated that the accuracy of clinical examination to establish the degree of bleeding and potential for internal damage after penetrating injury is poor [ 14 , 27 , 28 ]. Our clinical judgement in these patients is often obscured, as the scene of the incident is often not witnessed (making it hard to estimate the amount of blood loss), and the physiological response to blood loss in the patients may differ from non-penetrating injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Especially with peritoneal breeching, relative bradycardia may be present, obscuring the normal baroreceptor response. Therefore, all torso stab wounds should be considered as invasive until imaging is complete [ 14 ] and HEMS teams should have a low threshold to escort these patients to hospital, irrespective of their physiological state. However, given the small proportion of hemodynamically stable patients who need a HEMS intervention, the clinical team must perform a risk assessment, to include potential for clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury to any of these can place a person at immediate threat of severe disability or death, making chest trauma a well-acquainted adversary of emergency pre-hospital care providers. Even though significant chest injuries are associated with adverse outcomes, they can manifest late and have proven difficult to identify on clinical examination [ 2 , 3 ]. Leech et al [ 4 ] list closed tension pneumothorax (T-PTX) as the most common severe pathology in major chest trauma (1 in 250), a condition where air is increasingly introduced to the pleural space without an ability to escape [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite implementation of these protocols, rates of overtriage, to transfer a patient to a center with higher-than-necessary level, and undertriage, to transfer a patient to a lower-than-necessary trauma center level, are found to exceed 35% and 5%, respectively. [3][4][5][6][7][8] Appropriate and timely triage is crucial, as undertriage is associated with poor survival and overtriage poses a preventable burden to healthcare infrastructure. [8][9][10] The limited availability of information in the field may negatively impact the accuracy of triage decisions.…”
mentioning
confidence: 99%